Influenza vaccination in chronic inflammatory arthritis undergoing immunosuppressive treatments: temporal trend and factors of adherence. (21st October 2020) - Quartuccio, Luca; Zabotti, Alen; Gallo, Tolinda; De Vita, Salvatore; Valent, Francesca
Abstract: Objectives: To verify the level of adherence to the influenza vaccination program in a population of patients suffering from RA, PsA or AS undergoing immunosuppressive treatment. Methods: Administrative databases from the Regional Health Information System of Friuli Venezia Giulia (FVG), Italy, were used. Subjects were residents in FVG, suffered from chronic inflammatory arthritis and had at least one prescription for a DMARD in the 9 months before the start of the vaccination season (from 1 October to 31 December). The observation ranged from 2006 to 2018. Logistic regression was used to assess the association between vaccination and the patient's characteristics in the 2018–2019 influenza season. Results: Overall, vaccination adherence decreased from the highest value of 35.7% (662/1853) in 2006 to the lowest value of 25.3% (926/3663) in 2014; in people ≥65 years of age it also decreased over time from 61.6% (577/936) in 2008 to 43.9% (701/1595) in the 2014. By logistic analysis on the 2018–2019 season, which included 4460 patients, older subjects were more likely to be vaccinated [people 65–74 years, odds ratio (OR) 4.58 (95% CI 3.72, 5.64); people 75–84 years, OR 6.47 (95% CI 5.04, 8.32); both vs <65] as were those with diabetes [OR 1.66 (95% CI 1.05, 2.64)]. Treatment with a biologic agent alone [OR 0.64 (95% CI 0.52, 0.80)] and RA diagnosis [OR 0.69 (95% CI 0.51, 0.93)] were associated with lower adherence. Conclusion: Influenza vaccination adherence is alarmingly low in a population at higher risk of infectious complications, in particular in elderly patients.